Identification of Local Potential of South Kalimantan as a Source of Learning Fluid Physics - Misbah; Hamidah, Ida; Samsudin, Achmad; Qamariah; Abdul Rahman, Nor Farahwahidah (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
This study explores the integration of South Kalimantan’s local potential into fluid physics learning materials. Using a qualitative descriptive-exploratory design, the research employs observation, documentation, and literature review as data collection methods. Field observations focused on identifying local resources such as ironwood, floating houses, and floating markets, while interviews with physics educators provided additional insights. Data analysis involved thematic reduction and categorization to highlight key connections between local potential and fluid physics concepts, including hydrostatic pressure, Pascal's Law, and Archimedes' Principle. The findings demonstrate that local resources can be effectively incorporated into physics instruction, enhancing the relevance of abstract concepts for students and fostering deeper engagement with the material. The integration of local potential not only contextualizes learning but also promotes cultural awareness, making physics education more meaningful and connected to students' everyday experiences. This study offers valuable implications for curriculum development, emphasizing the importance of context-based, culturally responsive education in science.